Refugee entrepreneurship: systematic and thematic analyses and a research agenda - Abebe, Solomon Akele (Small business economics, 2023)
Refugee entrepreneurship has recently entailed increased scholarly mobilization and drastic growth in the volume of salient scientific research. However, this emerging research stream is marked by fragmentation and incoherence, primarily due to the multidisciplinary and context-specific nature of its extant findings. While this process is natural for emerging fields, the current state of research necessitates a comprehensive review, synthesis, and organization of its subject matter. Hence, this study systematically and thematically explores the landscape of refugee entrepreneurship research and its intellectual territory across diverse disciplines to take stock of a repository of the literature and trace its emergence, nature, and development. By analyzing 131 publications, this paper thus lays a collective research foundation for building a coherent theory, making incremental adjustments, and forming the ontological and epistemological basis for refugee entrepreneurship research. The study also identifies gaps in the literature and opens pathways for future scholarly endeavors. Plain English Summary Refugee entrepreneurship is an intriguing topic, providing a unique perspective for exploring the link between experiencing disruptive life events caused by being forced to leave one’s homeland and founding a new business in an unplanned country of resettlement. Refugee entrepreneurship has been of recent interest to researchers due to its potential to alleviate the grand socioeconomic challenges triggered by the “refugee crisis” of mid-2010s. Vigorous scholarly engagement has generated many publications on the topic. However, refugee entrepreneurship is not a well-developed research area because current knowledge is scattered across different fields, and there exists no unified conceptualization to understand refugee entrepreneurship activities. Hence, this study makes a comprehensive analysis and organization of its subject matter to create a common academic basis for future research. The principal implication of this study is that the scope for designing better refugee-integration policies should also involve a nuanced understanding of refugee entrepreneur/ship.